Media Preferences on Note-Taking among Pre-Service Language Teachers - David T. Loo (Researchparks Publishing, 2022)
Utilizing technology in the context of education is a common practice for effective instruction. Yet, advancements in the aspect of digital note-taking are too slow, despite of its necessity in a digital era where most information resources are lengthy and abundant, but also computerized and wireless. This puts pen-and-paper note-taking in an unfavorable circumstance as compared to note-taking that is digitally assisted. Various studies have surfaced to explore and develop digital tools for taking notes, as well as connecting gaps between pen-and-paper and technology-based note-taking. Unfortunately, it is still vague whether digital note-taking will and should replace the traditional note-taking, as there are flaws and shortcomings present in both medium. This study discussed the prevalent media preference of students when taking notes to determine which of the two note-taking methods are favored. Additionally, it also explores the usability of both note-taking methods, in order to investigate the deficiencies of their use and discuss implications for future note-taking applications. Developing effective note-taking software is problematic due to its complexity issues and suitability for productive learning. The study primarily inspected students’ perceived usability towards both note-taking methods and there is a total of 75 respondents who participated in the evaluation of their preferred media in taking notes. Based on the findings, traditional note-taking is prevalently utilized and favored compared to digital note-taking, but then, digital note-taking surpassed the overall usability score of pen-and-paper note-taking.